Two‐year outcomes from the Australian and New Zealand Emergency Laparotomy Audit‐Quality Improvement pilot study. Issue 12 (28th June 2021) - ,; James Aitken, R.; Griffiths, Ben; Van Acker, Jill; O'Loughlin, Edmond; Fletcher, David; Treacy, John P.; Watters, David; Babidge, Wendy J.
Abstract: Background: The aim of the Australian and New Zealand Emergency Laparotomy Audit‐Quality Improvement (ANZELA‐QI) pilot study was to determine (i) the outcomes of emergency laparotomy (EL) and (ii) the feasibility of a national, multi‐disciplinary quality improvement (QI) project based on a bundle of evidence‐based care standards. Methods: An online database was created using the Research Electronic Data Capture (REDCap) programme. National ethics approval with waiver of consent was obtained. Data were entered directly onto REDCap and extracted monthly for eight care standards (preoperative consultant radiologist reporting of computed tomography scans, preoperative mortality risk score, consultant presence in theatre, timely access to theatre and critical care commensurate with risk and involvement of aged care). Monthly QI run charts using 'traffic' light graphics (green ≥80%, amber ≥50% to <80% and red <50%) reported compliance with the standards. Results: Sixty hospitals indicated interest, but difficulties with site‐specific ethics approval resulted in only 24 hospitals participating (2886 EL in 2755 patients). The overall in‐hospital mortality was 7.1% (2.3%–13.3%) and average length of stay 15.5 (8.6–22.7) days. Both significantly declined. Preoperative risk assessment (overall 45%) improved almost three‐fold during the study. Only 60% had timely access to theatre and only 70% with a predicted mortality risk of >10% were admitted to critical care. Conclusion: Overall mortality compared favourably with similar international studies and declined in association with participation in the audit. Compliance with some care standards shows considerable scope to improve EL care using QI methodology. Abstract : This was a quality improvement (QI) study assessing emergency laparotomy in Australia. Whilst the 30‐day mortality was lower than that reported internationally, there was poor compliance with a 'bundle of care' that in other studies has been shown to significantly improve outcomes. It has also shown that national clinical QI studies are possible.